TECHNICAL AND ECONOMIC COMPARISON OF MODERN INTERMEDIATE BONDS - Karpushenko, M. I.; Antonov, M. I.; Velychko, D. V. (Science and Transport Progress, 2003)
The comparison of technical and economic parameters of modern intermediate fastenings is made and the prospect of their further development is analysed in this article.